Enhanced caffeine degradation by immobilised cells of Leifsonia sp. strain SIU - Ibrahim S.; Shukor M.Y.; Syed M.A.; Johari W.L.W.; Shamaan N.A.; Sabullah M.K.; Ahmad S.A. (Microbiology Research Foundation, 2024)
Indexed by WOS/ Scopus